Health-related quality of life and fear of progression in individuals with Li-Fraumeni syndrome - Kiermeier, Senta; Schott, Sarah; Nees, Juliane; Dutzmann, Christina; Strüwe, Farina; Kratz, Christian P.; Sauer, Christina; Fleischer, Anna; Keymling, Myriam; Maatouk, Imad (Journal of genetic counseling, 2024)
Li-Fraumeni syndrome (LFS) is a rare autosomal dominant cancer predisposition syndrome associated with a highly elevated lifetime cancer risk. This and the recommended intense surveillance program represent a large psychological burden on families. In order to develop targeted psychosocial interventions, we conducted a needs assessment. Adults (≥18 years) with LFS were included via regular hospital visits and online support groups and newsletters. Individuals filled out a questionnaire addressing among others: fear of progression (FoP-questionnaire, short-form), health-related quality of life (HRQoL, Short-Form Health Survey-12), distress (National Comprehensive Cancer Network distress thermometer), perceived cancer risk, and aspects of surveillance adherence. Collecting data over a 14-month period (March 2020 - June 2021), 70 adults were recruited (female = 58, 82.9%; mean age = 41.53 years). With mean mental component scores (MCS) of 42.28 (SD = 10.79), and physical component scores (PCS) of 48.83 (SD = 10.46), HRQoL was low in 34.8% (physical) and 59.4% (mental) of individuals when applying a mean cut-off of 45.4 (PCS) and 47.5 (MCS) to indicate poor HRQoL. High levels of FoP and distress were present in 68.6% and 69.1% of the participants, respectively. Performing a multiple linear regression on MCS and PCS, no sociodemographic variable was shown to be significant. FoP (β = −0.33, p < 0.05) and distress (β = −0.34, p < 0.05) were significantly associated with MCS. Individuals in our sample were burdened more than expected, with the majority reporting low levels of (mental) HRQoL, high distress, and FoP. Psychosocial support is necessary to help individuals with LFS (survivors as well as “previvors”) increase their HRQoL, as it is crucial to survival.
Gesehen am 19.08.2024